Pipe Support Welding Fabrication Process Using the Shielded Metal Arc Welding Method at PT XYZ - Prasetya, Herdi Eka; Hanifi, Rizal; Dirja, Iman; Sumarjo, Jojo (Universitas Sultan Ageng Tirtayasa, 2026)
This study presents the fabrication process of pipe support welding using the Shielded Metal Arc Welding (SMAW) method at PT Kinarya Gemilang Adhitama. The objective of this research is to examine the fabrication stages, identify the tools and materials involved, and analyze the key parameters that influence welding quality. The method employed is direct field observation during an industrial internship, supported by documentation and technical data collection in the workshop environment. The fabrication process includes material preparation, cutting, positioning, welding, cleaning, and quality control. Stainless steel SS 304 is used as the primary material, combined with SW 308 electrodes to ensure compatibility and corrosion resistance. The welding process is carried out using a DC inverter welding machine with controlled parameters, specifically a current of 220 A and a voltage of 46 V, to achieve optimal joint strength and stability. After welding, the cleaning process is conducted using a grinding tool to remove slag and impurities. Quality control is performed through visual testing and penetrant testing to detect surface defects such as cracks, porosity, and incomplete fusion. The results show that the SMAW method is effective and efficient for pipe support fabrication due to its flexibility, ease of application in various positions, and relatively low operational cost. Furthermore, the quality of the weld is highly dependent on welder skill, electrode selection, and proper parameter settings. Overall, the fabrication process meets industrial standards and produces reliable pipe support components suitable for piping systems.